FRI0634-HPR Non Attending Rheumatology Nursing Consultations, High Resolution of Urgent Demand. (9th June 2015) - Garcia Diaz, S.; Samper, E.; Roig Vilaseca, D.; Reina, D.; Cerda, D.; Estrada, P.; Navarro, V.; Torrente, V.; Corominas, H.
Abstract : Background: Patients with rheumatic diseases may require routine control and strict monitoring of their disease and side effects of treatment [1]. The possibility of providing nursing consultations for rheumatology patients via telephone or email rather than at clinic attendance [2], can potentially result in a lower rate of clinic visits, better informed and supported patients and families, more appropriate use of healthcare resources and real cost saving [3-5]. Objectives: To describe the content of the non-face consultations with rheumatology nursing. Methods: Descriptive study of a cohort of patients treated in the outpatient Rheumatology department at our Hospital. The period analysed was from January 2013 to December 2014. An Access database, specifically developed for this purpose, was used for data collection. The variables studied were age, sex, diagnosis, reason for query (doubts about their illness, medication, blood testing, other tests and/or administrative aspects) and query resolution. Nurses responded as soon as possible by telephone or via email between 8-15hrs Monday–Friday. SPSS v18 was used to analyse the data. Results: A total of 377 consultations were received, made by 217 patients, 74% of whom were women, diagnosed with Rheumatoid Arthritis (42%), Spondyloarthropathies (21%), Osteoporosis (15%), Systemic Lupus Erythematosus (2%), Osteoarthritis (2%) and other (18%); with a mean age of 57±14 years. Of these 217 patients, 84 of them consulted on more than one occasion. Of the 377 consultations, 361 consultations were made via telephone, 14 via email and 2 via text message. The reasons for the consultation can be divided into 5 categories (see Image 1 ). Of the 377 consultations, there were 399 reasons for consultation. 371 out of 377 consultations were resolved by the nurse, (131 without no help). In 240, the medical and/or other professional collaboration was necessary. Conclusions: The majority of queries were related to disease (flare up) or to medication. "Non attending" skilled nursing consultation, is shown to be an excellent alternative to face to face consultations, in the management of low complexity processes. It demonstrates a high degree of resolution that does not require an attending visit, thereby decreasing the rate of repeated visits to a rheumatologist. It also provides higher confidence, information and loyalty to patients and because of the overall reduction of patients at clinic visits, enables patients to access specialists when face to face consultations with a nurse or physician is needed. Few patients used email option for consultation and the possibility of promoting this alternative is considered. References: Valencian Rheumatology Nursing Society (GESVR), 2013. Najera C, et al. 2014. Hughes RA et al. 2002. Royal College of Nursing, 2006. Ferreira R et al. 2014. Acknowledgements: Claire Hale Disclosure of Interest: None declared